The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4236/fns.2019.1012101
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antidiabetic Activities of Probiotic Strains, <i>L. acidophilus</i> and <i>L. bulgaricus</i> against Fructose-Fed Hyperglycemic Rats

Abstract: Background: Deregulation of the gut microbiota results in various pathological disorders such as diabetes, inflammation, cancer, dyslipidemia etc. Modulation of intestinal microbiota by probiotics may facilitate the management of a number of clinical conditions of diabetes. Methods: The present study was designed to investigate the effect of feeding low-fat probiotic yogurt containing L. acidophilus and L. bulgaricus on fructose-fed hyperglycemic rats. Yogurt containing L. acidophilus or L. bulgaricus (9.5 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…According to a slew of research, probiotics can significantly reduce the risk of developing type 2 diabetes. [26] Sohag MSU et al [27] found that treatment of Probiotics reduced FBG in diabetic rats, which is consistent with our findings. Streptozotocin-induced diabetic mice were fed Probiotics, and their anti-hyperlipidemic effects were examined by Aggarwal J et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…According to a slew of research, probiotics can significantly reduce the risk of developing type 2 diabetes. [26] Sohag MSU et al [27] found that treatment of Probiotics reduced FBG in diabetic rats, which is consistent with our findings. Streptozotocin-induced diabetic mice were fed Probiotics, and their anti-hyperlipidemic effects were examined by Aggarwal J et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…Morphological, physiological and biochemical examination of probiotics suggested that the isolated strains from the commercial product 'Probio' were Lactobacillus (L) acidophilus (LAB-A) and L. bulgaricus (LAB-B) that all features consistent to previous reports [19,20]. This morphological characterization has already been published [21]. After preparation of yogurt by inoculating probiotic strain L. acidophilus or L. bulgaricus in low fat UHT liquid milk at 37°C for 48 hours, colonies were counted.…”
Section: Characterization Of Probiotic Strains For the Preparation Of Yogurt And Subsequent Colony Countsupporting
confidence: 77%
“…The combination of sodium alginate and maltodextrin increases the functional properties for the protection of diverse microorganisms (Krasaekoopt et al, 2003). According to literature, Lactobacillus platarum and Lactobacillus acidophilus are adequate probiotic candidates to prevent and ameliorate metabolic syndrome diseases such as type 2 diabetes (Sohag et al, 2019;Stevenson et al, 2014;Andrade-Velasques et al, 2021). Although there are previous reports in literature evaluating the development of chocolates with prebiotic, probiotic and synbiotic characteristics (Konar et al, 2016), there is scares information on the design of a chocolate formulations for the diabetic population, which should be sugarfree and also provide prebiotic and probiotic characteristics.…”
Section: Introductionmentioning
confidence: 99%